The effects of COVID-19 on Physical Medicine and Rehabilitation in Turkey in the first month of pandemic - YAĞCI, İLKER (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2020)
Objectives: The outbreak of novel coronavirus-2019 (COVID-19) has affected Turkey very seriously, as well as all around the world. Many urgent and radical measures were taken due to the high contagious risk and mortality rate of the outbreak. It is noteworthy that isolation recommendations and the provision of health services for pandemic have a negative impact on Physical Medicine and Rehabilitation (PMR) services. In this study, we aimed to evaluate the effects of COVID-19 on the PMR services and physiatrists immediately after the first month of pandemic in Turkey. Patients and methods: An online survey consisting of 45 items was sent to the members of the Turkish Society of Physical Medicine and Rehabilitation. The main goal of the survey was to evaluate the changes in the provided service of PMR and conditions of physiatrists one month after the first reported COVID-19 case in Turkey. Results: A total of 606 PMR specialists and residents responded to the survey. The mean number of the patients visited the outpatient clinics was 148.2 +/- 128.5 per week before the pandemic, it significantly decreased to 23.4 +/- 33.1 per week after the first month of the reported first COVID-19 case. Similarly, the mean number of the patients of inpatient service significantly decreased from 21.7 +/- 39.3 per week to 2.5 +/- 10.0 per week after the first month of the pandemic. Most of the residents (69%) reported that their training was seriously affected due to pandemic. From the economic aspect, 69.2% of the participants who were working at private hospitals reported a decrease in their monthly salary, and 21% of them were sent to an unpaid vacation. A total of 21.9% of private-practice institutions paused their services. During the first month, 46.9% of the participants were assigned to the different services such as COVID-19 inpatient service, emergency or COVID-19 outpatient clinics. According to the Republic of Turkey, Ministry of Health guideline and algorithm, 15.7% of the physicians were in the category of healthcare workers with suspected COVID-19. Conclusion: The COVID-19 pandemic affected seriously both the services and the PMR physicians as early as the first month. This effect is expected to become worse, when the duration of pandemic prolongs. Proper arrangements and measures should be planned to ameliorate the negative effects of the pandemic on the patients and PMR physicians.
Keywords: Coronavirus; COVID-19; pandemic; physical medicine and rehabilitation